2019
DOI: 10.1139/cjpp-2018-0736
|View full text |Cite
|
Sign up to set email alerts
|

Serum irisin level in myocardial infarction patients with or without heart failure

Abstract: This study aimed to assess serum irisin level in myocardial infarction (MI) with or without heart failure (HF) and the possible relation between irisin and cardiac markers, TNF-α and lipid profile. 86 subjects were included (33 patients had MI, 33 patients had MI with HF and 20 controls). Body Mass Index (BMI), waist/hip ratio (WHR), systolic and diastolic blood pressure (SBP and DBP), heart rate, left ventricular ejection fraction (LVEF) were measured. Blood samples were withdrawn on admission for measuring i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 54 publications
(33 reference statements)
1
25
1
Order By: Relevance
“…In heart, irisin improving mitochondrial functions protects cardiomyoblasts from various injuries characterized by elevated ROS production, i.e., ischemic and reperfusion [143], high glucose-induced [144], and lipotoxic-induced injury [145]. Moreover, human different reports have shown that irisin levels were lower in the diabetic patients with cardiovascular complications [146] and in subjects with myocardial infarction or heart failure [147]. Finally, in a mouse model of cardiac ischemia, irisin treatment reduces infarct size, promotes neo angiogenesis, and enhances the reestablishment of cardiac function [148].…”
Section: Irisin: Biological Rolementioning
confidence: 99%
“…In heart, irisin improving mitochondrial functions protects cardiomyoblasts from various injuries characterized by elevated ROS production, i.e., ischemic and reperfusion [143], high glucose-induced [144], and lipotoxic-induced injury [145]. Moreover, human different reports have shown that irisin levels were lower in the diabetic patients with cardiovascular complications [146] and in subjects with myocardial infarction or heart failure [147]. Finally, in a mouse model of cardiac ischemia, irisin treatment reduces infarct size, promotes neo angiogenesis, and enhances the reestablishment of cardiac function [148].…”
Section: Irisin: Biological Rolementioning
confidence: 99%
“…El-Mottaleb NA et al found irisin to be a useful biomarker in the diagnosis of myocardial infarction with or without heart failure [9]. The authors evaluated eighty-six subjects (33 patients with myocardial infarction, 33 patients with myocardial infarction and heart failure, and 20 controls) and found negative correlations between irisin and BMI, WHR, SBP, DBP, troponin-I, CK-MB, TNF-α, TC, TGs, and LDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…The blood concentration of irisin is significantly altered in patients suffering from acute coronary syndrome, especially in myocardial infarction (AMI), ST-Elevation Myocardial Infarction (STEMI) and stable coronary disease. Irisin seems to be a clinically promising marker reflecting cardiovascular system efficiency and the metabolic condition of the entire body of patients with CHF [8,9]. BIA as a non-invasive method reliably evaluates body composition and its nutritional status at the cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, FNDC5 overexpression significantly improved obesity-induced myocardial inflammation, fibrosis, oxidative stress, and cardiac remodeling [ 38 ]. Not only animal experiments, but some clinical studies also revealed that serum levels of irisin were decreased in subjects with heart failure, especially in those with reduced ejection fraction [ 12 , 39 ]. These findings show that irisin could be regarded as a promising biomarker and potential therapeutic target for cardiac injuries and remodeling.…”
Section: Discussionmentioning
confidence: 99%